Leptospira GAPDH liga plasmina(ogênio) humana que cliva substratos fisiológicos do hospedeiro (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is a zoonosis caused by spirochetes of the genus Leptospira. Leptospires have the ability to adhere to renal tubule cells, and to extracellular matrix components, which facilitates invasion and host colonization, also developed strategies to evade host´s complement system. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a multifunctional housekeeping protein, and an archetypical example of a moonlighting protein. Recent evidence identifies GAPDH as a requirement for fungal, protozoal, or viral virulence. Recent published data have shown that GAPDH presents plasminogen-binding activity.